Panji in Javanese court literature and beyond - Kumar, Ann (Wacana, Journal of the Humanities of Indonesia, 2020)
This article deals with Panji stories from Java, their original home. It begins with an examination of Panji as he appears in the Wangbaŋ Wideya, one of the earliest extant Panji stories, representing the culture of Majapahit and its successor states. It then goes on to survey a number of Panji compositions written by Pakubuwana IV, Sunan of Surakarta from 1788-1820, which reveal that Pakubuwana clearly identified with Panji, as opposed to say, Islamic models, or Western models, for the political realm possibly available at that time. The article goes on to look at the somewhat later writings of Yasadipura II (1756-1844) and Dipanagara, who led the 1825-1830 Java War against the Dutch. The former has a markedly bureaucratic, non-mythic approach to government. The latter does draw heavily on mythic validation, for instance from indigenous Javanese deities and from Islamic figures, but here too there is a notable lack of reference to Panji as an ideal. Panji theatre across Java and at the popular level is briefly surveyed, as is the extensive export of Panji stories to Malaysia, mainland Southeast Asia, and even possibly to Japan – which would suggest that they are far older than hitherto suspected.